Study of thermally coupled distillation systems for energy-efficient distillation - Saxena, Neha; Mali, Nilesh; Satpute, Satchidanand (Sadhana-Academy Proceedings in Engineering Sciences, 2017)
Distillation is one of the most widely used separation unit operations in process industries, although it is quite energy intensive. In many cases, the enormous energy requirements for distillation make it economically infeasible to carry out the separation. Thermally coupled distillation system (TCDS) is an advanced distillation method that provides significant energy savings of about 30% as compared with conventional distillation column sequences. The most well-known TCDS sequence, the Petlyuk configuration, has some operational challenges due to bidirectional vapour flow, which makes its implementation difficult in two-column mode. To overcome these limitations, a number of unidirectional vapour flow configurations have been proposed in the literature. The work on simulation analysis for such configurations is limited. In this paper, simulation models for two such configurations are developed, analyzed and compared with the Petlyuk and conventional distillation column sequences for separation of equimolar mixture of benzene-toluene-ethylbenzene.
Keywords: Distillation; energy efficient; Petlyuk; simulation; thermally coupled

Thermodynamic analysis and experimental validation of multi-composition ammonia liquor absorption engine cycle for power generation - Satpute, Satchidanand R.; Takalkar, Gorakshnath; Mali, Nilesh; Bhagwat, Sunil (International Journal of Energy Research, 2020)
Energy conservation, utilization, and effective integration are of utmost importance for future sustenance. Accordingly, this work focuses on the generation of power from the low-grade temperature below 150 degrees C. A proposed novel multi-composition ammonia liquor absorption engine (MALAE) power cycle can be used toward the above purpose by supplying renewable energy obtained from low concentration type solar collectors. Proposed MALAE power cycle minimizes heal loss due to heat recovery and uses high purity NH3 vapors to expand through the isentropic turbine. MALAE power system is modeled and simulated using NH3-H2O as a working fluid for a reboiler temperature of 115 degrees C. The purpose of this work is to simulate the proposed MALAE power cycle with the distillation column and two solution heat exchanger (SHE). MALAE modeling and simulation is accomplished in SCILAB software. The simulation outcome is validated with the pilot-scale 5 kW experimental setup and validation showed +/- 5% deviation. A comparison of MALAE cycle with published cycles signifies higher efficiency of MALAE cycle toward the utilization of low-grade energy from a temperature range of 100 degrees C to 150 degrees C. Finally, detailed parametric analysis of MALAE cycle efficiency is presented in terms of number of plates, distillation pressure and vapor flowrate, absorber temperature, pressure partial condenser temperature, and heat loads.
Keywords: absorption power cycle; ammonia water; low-temperature heat source; solar energy; Thermal Efficiency

Comprehensive review on catalytic O-alkylation of phenol and hydroquinone - Bhongale, Priyanka; Joshi, Sunil; Mali, Nilesh (Catalysis Reviews-Science and Engineering, 2023)
The alkylation process involves two competitive paths of O- and C-alkylation and achieving better selectivity for desired products is a very challenging problem. The development of new process for synthesis of O-methylated products of phenol and dihydric phenols is a subject of high industrial and academic interest. Alkyl phenyl ethers, especially anisole and 4-methoxyphenol, have captivated significant interest due to their increasing applications in pharmaceutical industries. The main emphasis of the present review is to explore the recent development in two catalytic O-alkylation processes. The first process is O-methylation of phenol into anisole and another is selective mono O-methylation of hydroquinone into 4-methoxyphenol. The present article covers O-alkylation methods with methanol and dimethyl carbonate as alkylating agent over various acidic and basic catalytic systems. The catalyst systems analyzed involves Bronsted and Lewis acidic and basic ionic liquids, conventional acids, metal oxides, solid acid and basic catalysts, hydrotalcites, various zeolites and heteropolyacids. The mechanistic behavior of alkylation reactions in presence of different catalytic system is reviewed critically which is important to design new and/or modified catalyst in order to maximize the yield of desired product. Additionally, an influence of reaction parameters, role of catalyst and their active sites on product distribution is described. The review paper gives useful insight for researchers in the field of catalysis and reaction engineering of alkylation reactions. Understandings of the reaction pathways will help in developing reliable kinetic models necessary for process scale-up to industrial scale reactor system.
Keywords: Dimethyl carbonate; Hydroquinone; Methanol; O-alkylation; phenol